THALASSEMIA AND NUTRITIONAL STATUS IN CHILDREN - Yoke Ayukarningsih; Jihan Amalia; Gita Nurfarhah (Journal of Health and Dental Sciences, 2022)
Thalassemia is an autosomal recessive single gene disorder due to an imbalance in the production of globin chains, namely α-globin and β-globin chains, which until now the case is increasing with manifestations of severe anemia and can have an impact on nutritional status. Malnutrition is one of the effects of thalassemia due to rapid erythrocyte turnover. The purpose of this paper is to discuss and provide information regarding the definition, epidemiology, classification, pathogenesis, diagnosis, complications, management, and nutritional status to minimize growth disorders in thalassemia patients. This research is a literature study, which is a type of research that collects, manages, uses, and reviews research data sourced from scientific research journals, previous research manuscripts, and textbooks. The results of the literature review are a factor of good nutritional status in thalassemia patients can be affected by various factors, one of which is increased energy expenditure which can offset good intake and consumption patterns. One of the assessments of nutritional status in thalassemia patients is the Upper Arm Circumference (UAC) because it can be used in organomegaly patients. Many factors can affect the nutritional status of children, especially in children with thalassemia. DOI : 10.54052/jhds.v2n1.p39-52